Midwifery students' experiences and expectations of using a model of holistic reflection. Issue 4 (July 2020) - Bass, Janice; Sidebotham, Mary; Creedy, Debra; Sweet, Linda
Abstract: Background: Reflective practice is a core professional competency and the hallmark of an autonomous, evidence-based midwife practitioner committed to lifelong learning. Despite this professional imperative little is currently known about how the development of reflective capacity is facilitated with midwifery students. Aim: This study aimed to determine (1) the extent to which a holistic, structured model of reflection develops reflective capacity in midwifery students; and (2) their perceptions of learning and teaching strategies that build reflective capacity. Design: A qualitative cross-sectional design involving focus groups and thematic analysis. Participants: The Bass Model of Holistic Reflection was introduced to promote development of reflective capacity in midwifery students enrolled in entry to practice programs in two Australian universities. Students were provided with guidance on how to apply the model to their reflections. After using the model for at least one trimester twenty-seven (27) participants volunteered to participate in focus groups. Findings: Four themes emerged 'safe space within a circle of trust', 'deep personal learning', 'consistency of application by skilled facilitators', and 'integration and connection'. Key conclusions and implications for practice: Use of a holistic model combined with integrative and structured reflective activities supports the scaffolded and developmental nature of reflection. Alignment of the model with a woman centred midwifery philosophy generates midwifery knowledge and reflects student expectations of their role as aspiring midwives. Midwives' attitudes regarding reflection influences students' perceptions of value. Quality of feedback provided by educators affects levels of student motivation and engagement with reflection.